Cognitive Behavioural Therapy for Chronic Fatigue Syndrome in a 15 year-old girl; A case-report - Vahdet GORMEZ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Abstract: Chronic Fatigue Syndrome (CFS) is a relatively common clinical condition that can cause sufferers to experience significant disability and distress, which may be further exacerbated by a lack of understanding from others, including health professionals. Cognitive behaviour therapy (CBT) has been widely researched and reported to be an evidence-based effective treatment approach for CSF. Cognitive-behavioural theory of CFS aims to describe how certain cognitions and behaviours could account for the symptoms, distress, and disability that maintain the illness. In this case study, a successful application of CBT in a 15-year-old young person with a twelve-month-history of disabling CFS is presented. We argue that for a clinical success, a non-judgemental approach to address the parental role in maintenance of the sick role is necessary. [JCBPR 2015; 4(2.000): 97-103]